The University of Los Llanos is projected in Europe (Contexto (Universidad de los Llanos), 2024)
The rector of the Universidad de los Llanos, Charles Robin Arosa, recently participated in the Executive Committee and General Assembly of the Association of Ibero-American Postgraduate Universities (AUIP), which took place in the city of Seville, Spain.At the international meeting, which brought together 104 rectors of higher education institutions from 15 countries, topics related to the Association's Action Plan were discussed and approved. In addition, the agenda included the presentation of different reports, and academic and social spaces were held, which allowed progress to be made mainly on topics such as research training, scholarships and international mobility, educational strengthening and innovation, and management, and institutional development, among others.
Keywords: international mobility; strengthening; educational innovation; training